2016
DOI: 10.1039/c5cy00944h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a post-synthetic method for tuning the Al content of OSDA-free Beta as a catalyst for conversion of methanol to olefins

Abstract: Zeolites synthesized without any organic structure-directing agent (OSDA) have several advantages over conventional zeolites synthesized with OSDAs. Their Al-rich compositions, however, are sometimes not suitable for applications as catalyst. In the present study, post-synthetic modification was performed upon an Al-rich Beta zeolite synthesized without any OSDAs (designated as "Beta(OF)") to obtain high-silica Beta zeolites. We have successfully developed a facile postsynthetic method for tuning the Al conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Both the aromatics and olefin cycles were revealed to function in the reaction 19d,84. Otomo et al prepared a series of dealuminated high‐silica Beta via high‐temperature calcination and acid treatment . They found that the propylene selectivity could achieve 37.4–49.7% over the material with a Si/Al ratio of 112.…”
Section: Toward Enhanced Ethylene or Propylene Selectivitymentioning
confidence: 99%
“…Both the aromatics and olefin cycles were revealed to function in the reaction 19d,84. Otomo et al prepared a series of dealuminated high‐silica Beta via high‐temperature calcination and acid treatment . They found that the propylene selectivity could achieve 37.4–49.7% over the material with a Si/Al ratio of 112.…”
Section: Toward Enhanced Ethylene or Propylene Selectivitymentioning
confidence: 99%
“…The peak at −53 ppm in the 27 Al MAS NMR demonstrates the formation of tetrahedral coordination environment Al(OSi) 4 − , meanwhile, the absence of the bond at 0 ppm suggests that there is not octahedral coordination aluminum in the V‐Si‐Al gel. Furthermore, the band at 561 cm −1 of FTIR spectra of the aged V‐Si‐Al gel ascribes to vibration of double 5‐members ring (Figure b), which demonstrates the formation of secondary structure units of ZSM‐5 through the further condensation of TO 4 (T=Si or Al)in the V‐Si‐Al gel ,…”
Section: Resultsmentioning
confidence: 94%
“…Structural modification after synthesis is commonly used to achieve a better hierarchical structure. Acid or alkaline treatment can help the dealumination process and generate mesopores . A fluoride ion treatment helps the reconstruction of crystal structures.…”
Section: Improving Transport Efficiency By the Application Of Discretmentioning
confidence: 99%